Allelopathic effects of leaf extracts of Eucalyptus camaldulensis Dehnh. on morphological, physiological, and yield traits of Ethiopian wheat (Triticum durum L.) cultivars - Animut Mekuriaw Andualem; Mersha Wubie Aragaw; Abiyu Enyew Molla; Zelalem Getnet Tarekegn; Getinet Masresha Kassa (BMC Plant Biology)
Abstract Allelochemicals released into the soil from the leaves of eucalyptus species affect the growth and physiology of various crops. This study aimed to evaluate the allelopathic effects of aqueous and methanolic leaf extracts from Eucalyptus camaldulensis on three Ethiopian wheat cultivars (Assasa, Mukiye and Ude) of Triticum durum L. It was conducted as a pot experiment, and it utilized four concentrations of the extracts (Control (0%), 10%, 15%, and 20%) in a completely randomized design with three replicates. Results indicated that both extracts inhibited plant growth, biomass, and yield, with the methanolic extract showing stronger inhibitory effects. For instance, a concentration of 20% methanolic leaf extracts decreased chlorophyll fluorescence in the Assasa, Ude, and Mukiye cultivars by 53.97%, 36.36%, and 36.51%, respectively. The growth of both shoots and roots in Assasa, Ude, and Mukiye was significantly reduced at higher concentrations. Increasing concentrations of the extracts led to greater reductions in seedling traits and overall crop yield, with significant impacts observed (p ≤ 0.05). The findings suggest that eucalyptus should not be planted on agricultural land due to its negative impact on crop productivity.